PENGARUH METODE ROLE PLAYING MENGGUNAKAN CERITA KETELADANAN PAHLAWAN BANGSA TERHADAP PENANAMAN NILAI-NILAI PANCASILA PADA SISWA KELAS IV DI SD NEGERI 3 PULAU RIMAU - Makdalena Frisda; Ramanata Disurya; Adrianus Dedy (STKIP Subang, 2023)
This study aims to determine the effect of the role playing method using the exemplary story of the nation's heroes on Pancasila values in fourth grade students at SD Negeri 3 Pulau Rimau. with the experimental method, namely Pre-Experimental Design with the type of research design One-Group Pretest-Posttest Design. The population in this study were all 23 students of grade IV. Determination of the research sample using total sampling technique, namely the sample is all members of the population used as a sample. The test instrument used was an essay test in the form of a pretest and posttest with 5 questions. The results of this study indicate that there is an influence of the role playing method using the exemplary story of the nation's heroes on the inculcation of Pancasila values in fourth grade students at SD Negeri 3 Pulau Rimau in 2023 with an average pretest score of 56.09 and a posttest result of 90. 00. Based on the calculation of the t test, it is obtained tcount > ttable or -13.597 > 2.074 with a significant level (a) of 0.05. In accordance with hypothesis testing, that is, if tcount > ttable then Ha is accepted and H0 is rejected.